2018
DOI: 10.1186/s12974-018-1287-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tryptase on mouse brain microvascular endothelial cells via protease-activated receptor 2

Abstract: BackgroundMast cells (MCs), the ‘first responders’ in brain injury, are able to disrupt the blood–brain barrier (BBB), but the underlying mechanism is not well understood. Tryptase is the most abundant MC secretory product. Protease-activated receptor 2 (PAR-2) has been identified as a specific receptor for tryptase, which is abundantly expressed in brain microvascular endothelial cells. The BBB comprises brain microvascular endothelial cells that display specialised molecular properties essential for BBB func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 37 publications
3
14
0
Order By: Relevance
“…Thus, our results were in line with previous data indicating the MC-tryptase-dependent expression of PAR-2 [37,49]. In addition to the evidence suggesting linked expression of PAR-2 to MC-tryptase [37], the ability of MC-tryptase to upregulate the protein expression of PAR-2 [49] as well as a positive correlation between their expression levels were proposed in earlier studies [37,[55][56][57]. However, despite our extensive research, we could not encounter literature evidence unveiling how MC-tryptase acts as a regulator on PAR-2 protein expression [49].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, our results were in line with previous data indicating the MC-tryptase-dependent expression of PAR-2 [37,49]. In addition to the evidence suggesting linked expression of PAR-2 to MC-tryptase [37], the ability of MC-tryptase to upregulate the protein expression of PAR-2 [49] as well as a positive correlation between their expression levels were proposed in earlier studies [37,[55][56][57]. However, despite our extensive research, we could not encounter literature evidence unveiling how MC-tryptase acts as a regulator on PAR-2 protein expression [49].…”
Section: Discussionsupporting
confidence: 93%
“…We also provided in vivo evidence demonstrating that PAR-2 expression in the brain was linked to MC-tryptase given the attenuated PAR-2 expression in response to the selective inhibition of MC-tryptase with APC366 following CA. Thus, our results were in line with previous data indicating the MC-tryptase-dependent expression of PAR-2 [37,49]. In addition to the evidence suggesting linked expression of PAR-2 to MC-tryptase [37], the ability of MC-tryptase to upregulate the protein expression of PAR-2 [49] as well as a positive correlation between their expression levels were proposed in earlier studies [37,[55][56][57].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Further, MCs are powerful and fast sensors of brain injury [15][16][17] by releasing cytoplasmic secretory granules filled with immune and inflammatory mediators including histamine, β-tryptase, tumor necrosis factor-alpha (TNF-α), and interleukin-(IL-) 1β [18]. MCs also express receptors and ligands of various inflammatory pathways, including protease-activated receptor-2-(PAR2-) MAPK-NF-kappa B, histamine receptor 1 (H1R)/H4R-MAPK, and PI3K/AKT-NF-kappa B pathways [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that MC β-tryptase could activate proteinase-activated receptor 2 receptors, which contribute to the degradation of tight junction proteins, in brain microvascular endothelial cells [20]. Furthermore, microglia express all four histamine receptors (H1R, H2R, H3R, and H4R), and stimulation of mitogen-activated protein kinases (MAPK), PI3K/AKT, and nuclear factor kappa B (NF-kappa B) signaling pathways through H1R and H4R leads to the production of TNF-α and IL-6 [19,34,35].…”
mentioning
confidence: 99%